INFLATION ON ECONOMIC GROWTH IN GORONTALO - Sitti Nurul Hidayah; Siti Rahmatia Napu (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
One measure of effective development is economic growth. Economic growth is the process by which the real gross national product or real national income rises. This study is a form of quantitative study. The goal of this research is to investigate how inflation affects economic growth. According to the findings of this study, the inflation variable has a significant value of 0.280, which is larger than 0.05. It is possible to conclude that the inflation variable has no effect on economic growth.The t-count value is 1.314, and the t-table value is 3.18245. Consequently, the t-count is less than the t-table, indicating that the inflation variable has no meaningful effect on economic growth. The preceding reasoning demonstrates that inflation reduces economic growth year after year. Keywords: Inflation, Economic Growth